Motor Training After Stroke: A Novel Approach for Driving Rehabilitation - Lodha, Neha; Patel, Prakruti; Casamento-Moran, Agostina; Christou, Evangelos A. (Frontiers in Neurology, 2022)
Background: A key component of safe driving is a well-timed braking performance. Stroke-related decline in motor and cognitive processes slows braking response and puts individuals with stroke at a higher risk for car crashes. Although the impact of cognitive training on driving has been extensively investigated, the influence of motor interventions and their effectiveness in enhancing specific driving-related skills after stroke remains less understood. We compare the effectiveness of two motor interventions (force-control vs. strength training) to facilitate braking, an essential skill for safe driving. Methods: Twenty-two stroke survivors were randomized to force-control training or strength training. Before and after training, participants performed a braking task during car-following in a driving simulator. We quantified the cognitive and motor components of the braking task with cognitive processing time and movement execution time. Results: The cognitive processing time did not change for either training group. In contrast, the movement execution became significantly faster (14%) following force-control training but not strength training. In addition, there were some specific training-related changes in each group. The force-control group showed improved accuracy and steadiness of ankle movements, whereas the strength training group showed increased dorsiflexion strength following training. Conclusion: Motor intervention that trains ankle force control in stroke survivors improves the speed of movement execution during braking. Driving rehabilitation after stroke might benefit from incorporating force-control training to enhance the movement speed for a well-timed braking response.